Reading in Early Adolescence Impact on Cognitive Development (Wire Insights: Journal of Innovation Insights, 2024)
According to the definition of ontogeny psychology, early adolescence includes 15-18 years of age. The complexity of the modern age is also reflected in the new positions of young people in the social environment and the complex process of adapting to these positions. In this period of adolescence, the exaggerated reflection (fantasy) in the imagination process is also noteworthy.